Methodical Aspects of Preparation of the Future Educators of Preschool Educational Establishments - Davkush, Nataliya (Pedagogical Discourse, 2011)
Peculiarities of preparation of the future educators of preschool educational establishments to self-knowledge, self-develobment and self-perfection are examined in the article. The author offers the method of preparation of specialists of preschool type to self-knowledge, self-develobment and self-perfection. Examples of problem questions, directed to perfection of the mentioned functions of the future teachers are given.